THERAPEUTIC MANAGEMENT AND CHANGES IN THE ENDOMETRIUM OF REPEAT BREEDING COWS - PATEL, J A; DHAMI, A J; KAVANI, F S; PANCHAL, M T; GHODASARA, D J (The Indian Journal of Animal Reproduction, 2023)
The overall incidence of repeat breeding observed among 98 breedable Holestein Friesian (HF) animals of a farm was 40.82 % (n=40). These 40 repeat breeding cows were divided at random In different groups with a view to evaluate the relative efficacies of different hormonal therapies at breeding towards improving their reproductive efficiency over the control. The conception rate following i/m treatment at the time of insemination with GnRH (Receptal, Busere/ln acetate, 0.02 mg), LH (Chorulon, 1500 IU) and Progesterone (Proluton depot, 500 mg) was 66.66, 83.33 and 50.00 %, respectively, with an overall mean of 66.66 % (12/18). This was significantly higher (P<0.01) than that (33.33%, 2/6) obtained in control untreated repeat breeding cows. The overall conception rate in the treatment cycle itself was significantly (P<0.01 ) higher than in untreated control group (55.55 vs 16.66%). Further, out of 10 chronic repeat breeding cows treated ’:Vith PGF 2a (Vetmate, 2 ml) at mid-cycle, 9 (90%) cows came in estrus within 80 hrs of treatment and 33.33 % (n=3) conceived at first estrus following GnRH treatment (0.01 mg i/m) at second insemination 12 hrs apart. Out of 18 endometrial biopsy samples collected from right and left horns and body of the uterus of 6 culled repeat breeding cows, chronic endometritis was detected in 12 samples (4 animals) and sub-acute endometritis in 6 samples (2 animals). No significant difference could be observed in histopathological changes pertaining to endometrial biopsies from left and right uterine horns and uterine body. Although almost identical changes were seen at all the 3 sites of the uterus, however, microscopic. lesions between animals differed. The endometrial biopsy proved a good guide to decide the prognosis of chronic repeat breeding animals and GnRH or LH can be recommended along with A! to improve fertility in infertile cows.